MuPix8: large area monolithic HVCMOS pixel detector for the Mu3e experiment - Augustin, Heiko; Dittmeier, Sebastian; Hammerich, Jan; Herkert, Adrian; Huth, Lennart; Kröger, Jens; Meier Aeschbacher, Frank; Schöning, André; Weber, Alena; Wiedner, Dirk (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2019)
The requirements of the ultra thin pixel detectors for the Mu3e experiment at PSI can be achieved by the HVCMOS technology, which allows the design of fast monolithic detectors. The latest nearly full size prototype, MuPix8, has a size of about 1 × 2 cm2. The pixel readout circuitry was fully redesigned in comparison to the previous MuPix versions. MuPix8’s readout electronics implement a new concept with two comparators and two different operation modes. One mode uses two threshold voltages for time walk correction, the other is a ramp-ADC. First tests show a detection efficiency of 99.6% for 4 GeV electrons.
Gesehen am 04.07.2019
Available online 26 September 2018